Discursive variants and variations of the term “judge” in the Romanian legal order - Botezatu, Vanina Narcisa (Estudios de Traducción, 2023)
Legal translations to and from another language have always been a topic of debate due to the diversity and complexity of legal systems. In order to ensure a correct understanding of rights and obligations it’s not only necessary to know the terminology, but also how expressions and concepts are performative within the legal system. The present article shall analyse the second part of the terminology that includes the term judge, using as support the database of EurLex, InfoCuria, as well as sentences that can be found on the portal of Romanian courts.